When Getting There is Not Enough: A Nationwide Cross-Sectional Study of 998 Maternal Deaths and 1451 Near-misses in Public Tertiary Hospitals in a Low-income Country. Issue 1 (March 2017) - Oladapo, O.T.; Adetoro, O.O.; Ekele, B.A.; Chama, C.; Etuk, S.J.; Aboyeji, A.P.; Onah, H.E.; Abasiattai, A.M.; Adamu, A.N.; Adegbola, O.; Adeniran, A.S.; Aimakhu, C.O.; et al.
Abstract : ( BJOG. 2016;123:928–938) Achieving the fifth Millennium Development Goal (MDG-5) to reduce maternal mortality rates is a challenge in some low-income countries due to the lack of reliable data to evaluate progress and guide the appropriate actions. The aim of this study, the Nigeria Near-miss and Maternal Death Survey, was to determine the burden of maternal death and maternal near-miss occurrences through surveillance and data collection of life-threatening maternal complications or severe maternal outcomes (SMO) from Nigerian public tertiary hospitals.